2008
DOI: 10.1136/ard.2008.089979
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity does not influence treatment with etanercept in patients with ankylosing spondylitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
78
1
9

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 16 publications
9
78
1
9
Order By: Relevance
“…Applying the MA-ETN63C8/MA-ETN61C1-HRP ELISA, mean ETN concentration in the 21 AS patient samples was 3.8 mg/ml (SD 2.2 mg/ml) at 24 wk of treatment. This finding is more or less in line with previous studies in AS (4,(18)(19)(20), in which mean ETN concentrations of ∼3 mg/ml were reported at 24 wk of therapy. In these studies, ETN was also captured through its ability to bind TNF; however, the set-up differed slightly from the TNF-coated ELISA described in this article, because a specific mouse mAb was used to immobilize TNF on the plate.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Applying the MA-ETN63C8/MA-ETN61C1-HRP ELISA, mean ETN concentration in the 21 AS patient samples was 3.8 mg/ml (SD 2.2 mg/ml) at 24 wk of treatment. This finding is more or less in line with previous studies in AS (4,(18)(19)(20), in which mean ETN concentrations of ∼3 mg/ml were reported at 24 wk of therapy. In these studies, ETN was also captured through its ability to bind TNF; however, the set-up differed slightly from the TNF-coated ELISA described in this article, because a specific mouse mAb was used to immobilize TNF on the plate.…”
Section: Discussionsupporting
confidence: 81%
“…However, anti-ETN Abs were not detected in any of the patient sera tested, which seems to support the hypothesis that ETN is not or only marginally immunogenic (18). Although there is a possibility that some positive results were missed as a result of interference of drug in the sample, the overall reported frequency of anti-ETN Abs is low (19).…”
Section: Discussionmentioning
confidence: 63%
“…The authors confirm at least 10 years of observations that immunogenicity most notably with monoclonal antibody therapies results in treatment failure [1]. By contrast, receptor-based constructs seem less likely to be associated with the development of patient-derived antibody failure [2][3][4]. Also as pointed out by the authors, the development of neutralizing antibodies is independent of underlying immune disease.…”
supporting
confidence: 72%
“…de Vries и со-авт. [24] показали, что концентрация ЭТЦ в сыворотке не взаимосвязана с клиническим ответом. У некоторых па-циентов, получавших ЭТЦ, в сыворотке были обнаруже-ны антитела к препарату.…”
Section: Discussionunclassified